Evaluation of Physicochemical Properties of Amphiphilic 1,4-Dihydropyridines and Preparation of Magnetoliposomes - Petrichenko, Oksana; Plotniece, Aiva; Pajuste, Karlis; Rucins, Martins; Dmitrijevs, Pavels; Sobolev, Arkadij; Sprugis, Einars; Cebers, Andrejs (MDPI, 2021)
This study was focused on the estimation of the targeted modification of 1,4-DHP core with (1) different alkyl chain lengths at 3,5-ester moieties of 1,4-DHP (C12, C14 and C16); (2) N-substituent at position 1 of 1,4-DHP (N-H or N-CH3); (3) substituents of pyridinium moieties at positions 2 and 6 of 1,4-DHP (H, 4-CN and 3-Ph); (4) substituent at position 4 of 1,4-DHP (phenyl and napthyl) on physicochemical properties of the entire molecules and on the characteristics of the obtained magnetoliposomes formed by them. It was shown that thermal behavior of the tested 1,4-DHP amphiphiles was related to the alkyl chains length, the elongation of which decreased their transition temperatures. The properties of 1,4-DHP amphiphile monolayers and their polar head areas were determined. The packing parameters of amphiphiles were in the 0.43–0.55 range. It was demonstrated that the structure of 1,4-DHPs affected the physicochemical properties of compounds. “Empty” liposomes and magnetoliposomes were prepared from selected 1,4-DHP amphiphiles. It was shown that the variation of alkyl chains length or the change of substituents at positions 4 of 1,4-DHP did not show a significant influence on properties of liposomes.---//---This work is licensed under a CC BY 4.0 license.
This work was ﬁnancially supported by PostDocLatvia Project No 1.1.1.2/VIAA/1/16/018 (O. Petrichenko: TGA and DTA analysis, magnetic nanoparticles synthesis, preparation and characterization of magnetoliposomes), PostDocLatvia Project No 1.1.1.2/VIAA/2/18/371 (M. Rucins:synthesis and characterization of 1,4-DHP amphiphiles), LIOS internal grant IG-2018-13 (P. Dimitrijevs: LB measurements) and M.era-net project FMF No.1.1.1.5/ERANET/18/04; Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART²
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; 1,4-dihydropyridine amphiphiles; iron oxide nanoparticles; magnetoliposomes; lipid monolayers; physicochemical properties